2018
DOI: 10.1080/15384101.2018.1431597
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic analyses of microRNA-targeted genes and microarray-identified genes correlated with Barrett's esophagus

Abstract: Barrett's esophagus (BE) is defined as a metaplasia condition in the distal esophagus, in which the native squamous epithelium lining is replaced by a columnar epithelium with or without intestinal metaplasia. It is commonly accepted that BE is a precancerous lesion for esophageal adenocarcinoma. The aim of this study was to investigate the aberrant microRNAs (miRNAs) and differentially expressed genes (DEGs) associated with BE based on online microarray datasets. One miRNA and five gene expression profiling d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Numerous studies related to EAC and BE have been conducted over the last decades, and more attention should be paid to the pathogenesis and the molecular mechanisms involved in the progression of BE and EAC, which could help in prevention and improve prognosis[19]. Currently, histological examinations are the golden standard for the diagnosis of EAC and BE; however, the inter- and intra-observer variabilities are not ideal[20].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies related to EAC and BE have been conducted over the last decades, and more attention should be paid to the pathogenesis and the molecular mechanisms involved in the progression of BE and EAC, which could help in prevention and improve prognosis[19]. Currently, histological examinations are the golden standard for the diagnosis of EAC and BE; however, the inter- and intra-observer variabilities are not ideal[20].…”
Section: Discussionmentioning
confidence: 99%
“…The online software JASPAR (http://jaspar.genereg.net/) 27 and meme-FIMO (http://meme-suite.org/) 28 were utilized to predicate SMAD3 binding sites on the HCP5 promoter. Additionally, we used miRDB database (http://www.mirdb.org/) 29 to analyze whether HCP5 is contained complementary region of the miRNA 'seed' sequence.…”
Section: Methodsmentioning
confidence: 99%
“…MELK is an oncogenic kinase essential for early recurrence of hepatocellular carcinoma (Xia et al, 2016). Studies have shown that MELK is a novel biomarker and a potential therapeutic target in cervical cancer (Lv et al, 2018), triple-negative breast cancer (Moreno, 2016) and gastric cancer (Zhang et al, 2016a). NDC80 (Nuclear division cycle 80) is also known as highly expressed in cancer 1 (HEC1).…”
Section: Discussionmentioning
confidence: 99%